Photodynamic Therapy: A View through Light - Dave, Deepak; Desai, Urmi; Despande, Neeraj (Journal of Orofacial Research, 2012)
The removal of biofilm and mineralized deposits from the tooth surface are the fundamental aspects of periodontal therapy. Using antimicrobial agents to treat periodontitis withoutdisruption of the biofilm ultimately results in treatment failures. It is difficult to maintain therapeutic concentrations at the target sites and target organisms may develop resistance to drugs. Photodynamic therapy (PDT) is a mechanism which destroys target cells by reactive oxygen species produced by photosensitizing compounds and light of an appropriatewavelength. The advantage of this new approach includes rapid bacterial elimination, minimal chance of resistance development and safety of adjacent host tissue and normal microflora. Thus, the available knowledge of photodynamic therapy should encourage a more clinically oriented application of this technique.